Peran Penting E-Business dan E-Commerce dalam Meningkatkan Daya Saing Pemasaran di Bank Syariah - Angger Gumilang Sugiarto; Parulian Sibuea; Fitra Amar Rosuli; M. Aidil Syahputra; Asnawi (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
E-business and e-commerce have grown rapidly and become the main foundation for many companies around the world. The research conducted using qualitative methods of data taken books, notes and reports on previous research results. Bank is a financial intermediary institution or commonly called financial intermediary. This means that a bank institution is an institution whose activities are related to money problems. Liquidity, rentability and solvency of Islamic banks have been achieved. Sharia financial institutions carry out their business activities based on Islamic principles, freedom of Islamic principles. Islamic financial institutions have the goal of implementing development matters to improve justice and equitable distribution of people's living standards. The implementation of E Business carried out by the banking sector is influenced by several factors such as technological readiness or competence, bank size, commitment to financial resources, alignment of IT/Business strategies, adequacy of IT professionals, availability of online income